DIALEKTIKA AGEN DAN STRUKTUR DALAM PENGELOLAAN LAHAN PERTANIAN DI TINGKAT LOKAL (Studi tentang Strukturasi dalam Pemaknaan Lahan Pertanian Oleh Masyarakat Petani Simandame Pematang Raya dan Respon terhadap Program Pembangunan Ibukota Kabupaten Simalungun yang Baru) - , Ruth Agnesia Sembiring, S.Sos., Miftah Adhi Ikhsanto, Mi.OP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to reveal how the agrarian lifestyle continues to be practiced by the community, even when they developed the area into a new capital of the regency. Community interpret farm management as a form of love towards the family. Agricultural land is also considered as a major economic resource in people's lives. This study was carried out on Simandame agricultural land, Pematang Raya, Raya Subdistrict, Simalungun Regency, North Sumatra Province. Simandame agricultural land area of approximately 100 Hectares and involving more than 100 (one hundred) landowners. The Local Government asked the Simandame farming community selling the land to Local Governments for the implementation of the development program. While overall, the agricultural sector is a sector that is very important to people's lives in Pematang Raya. This study uses Giddens Structuration Theory to explain how an agrarian lifestyle continues to be practiced by Pematang Raya society even though they are dealing with the development program. Agrarian lifestyle practiced in social life, repeated in cross space and time is the structure. Agrarian lifestyle is a structure of signification involving symbolic schemata, meaning, and discourse. Pematang Raya communities that adhere to the structure of the continuous flow of actions and events referred to as actors (agents). The study concludes that the development program at the expense of agricultural land belonging to the community in Pematang Raya not absolute change agrarian lifestyle that had been practiced by the community. Pematang Raya is constantly evolving as the Capital of Simalungun Regency but the society still largely agrarian society. The absence of conflict in the sales process Simandame Agricultural Land because of the dialectic of control between the community and Local Government.